RIFM fragrance ingredient safety assessment, 3, 3-dimethyl-5-(2, 2, 3-trimethyl-3-cyclopenten-1-yl)-4-penten-2-ol, CAS Registry Number 107898-54-4. (December 2019) - Api, A.M.; Belsito, D.; Biserta, S.; Botelho, D.; Bruze, M.; Burton, G.A.; Buschmann, J.; Cancellieri, M.A.; Dagli, M.L.; Date, M.; Dekant, W.; Deodhar, C.; et al.
Highlights: 3, 3-Dimethyl-5-(2, 2, 3-trimethyl-3-cyclopenten-1-yl)-4-penten-2-ol; a safety assessment based on RIFM's criteria. A safety assessment based on 7 human health endpoints plus environmental. All endpoints were cleared using target data, read-across, and/or TTC.